Analysis of The Influence of Dividend Policy On The Value of Manufacturing Companies at PT Bess Listed On The Idx - Sulastriningsih Sulastriningsih; Nursiyami Nursiyami; Rusmiyatun Rusmiyatun (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of dividend policy on mark company on company manufacturing PT BESS which registered in Exchange Effect Indonesia (BEI). Research methods the method used is quantitative method with an associative approach. Research data was obtained from the Stock Exchange report Indonesia (BEI) 2021-2025 through the official website of the Indonesia Stock Exchange (BEI) www.idx.co.id .The data analysis technique used is simple correlation descriptive statistical analysis , regression linear simple , determination test, and t-test . Analysis statistics descriptive used For describe variables in research This. Analysis regression linear simple aiming For know the magnitude influence policy dividend to mark company.Results study show that hypothesis Which state There is the influence of dividend policy on the value of the listed manufacturing company PT BESS on the Stock Exchange Indonesia (IDX) year 2021-2025 can proven by mark t count > t table = 854 > 805. R value = 924 shows that, the relationship (correlation) between policy dividends with company values manufacturing Which listed on the Indonesia Stock Exchange (IDX) in 2021-2025 is strong and positive. The more big policy dividend so the more increase mark company, Likewise, conversely, the smaller the dividend policy, the more it decreases. company value. The Adjusted R Square value = 805 shows that the contribution Which donated policy dividend to mark company manufacturing registered in stock Exchange Indonesia (IDX) year 2021-2025 is 14.6%.